A Phase 1b Study Evaluating the Safety, Tolerability, and Immunogenicity of CMB305, a Lentiviral-Based Prime-Boost Vaccine Regimen, in Patients with Locally Advanced, Relapsed, or Metastatic Cancer Expressing NY-ESO-1. (1st January 2020) - Somaiah, Neeta; Chawla, Sant P.; Block, Matthew S.; Morris, John C.; Do, Khanh; Kim, Joseph W.; Druta, Mihaela; Sankhala, Kamalesh K.; Hwu, Patrick; Jones, Robin L.; Gnjatic, Sacha; Kim-Schulze, Seunghee; et al.
ABSTRACT: Preclinical data suggest that a "prime-boost" vaccine regimen using a target-expressing lentiviral vector for priming, followed by a recombinant protein boost, may be effective against cancer; however, this strategy has not been evaluated in a clinical setting. CMB305 is a prime-boost vaccine designed to induce a broad anti-NY-ESO-1 immune response. It is composed of LV305, which is an NY-ESO-1 expressing lentiviral vector, and G305, a recombinant adjuvanted NY-ESO-1 protein. This multicenter phase 1b, first-in-human trial evaluated CMB305 in patients with NY-ESO-1 expressing solid tumors. Safety was examined in a 3 + 3 dose-escalation design, followed by an expansion with CMB305 alone or in a combination with either oral metronomic cyclophosphamide or intratumoral injections of a toll-like receptor agonist (glucopyranosyl lipid A). Of the 79 patients who enrolled, 81.0% had sarcomas, 86.1% had metastatic disease, and 57.0% had progressive disease at study entry. The most common adverse events were fatigue (34.2%), nausea (26.6%), and injection-site pain (24.1%). In patients with soft tissue sarcomas, a disease control rate of 61.9% and an overall survival of 26.2 months (95% CI, 22.1–NA) were observed. CMB305 induced anti-NY-ESO-1 antibody and T-cell responses in 62.9% and 47.4% of patients, respectively. This is the first trial to test a prime-boost vaccine regimen in patients with advanced cancer. This approach is feasible, can be delivered safely, and with evidence of immune response as well as suggestion of clinical benefit.